Construction of an evaluation system for the effectiveness of rural sewage treatment facilities and empirical research - He, Yuxiao; Yang, Lu; Xu, Huashan; Han, Xu; Sun, Changlei; Di, Yanming; Zhao, Tongqian (Frontiers in Environmental Science, 2024)
Rural domestic sewage treatment is an important starting point to improve the quality of rural ecological environment, an important part of new rural construction, and an inherent requirement to promote rural economic development. The operation of rural sewage treatment facilities is not good, and there is a lack of long-term operation guarantee and supervision mechanism. It is urgent to carry out research on the evaluation index system, evaluation method and evaluation benchmark of the operational effect of rural sewage treatment facilities. This article used rural sewage treatment facilities in a city in northern China as the research object and constructed an evaluation method for the operational effectiveness of rural sewage treatment facilities. This study selected evaluation indices from three perspectives: economy, technology and management, which are divided into two stages: planning and operation. A judgment matrix was constructed using the analytic hierarchy process, and index weights were calculated using Yaahp10.3 software to determine evaluation criteria.Fifteen rural sewage treatment plant stations were selected to evaluate their planning and operation effects. The results of the weight assignment show that the weight of the COD removal rate, operating load rate and operating cost indexes are high, in line with the actual evaluation of the effectiveness of rural sewage treatment facilities at different stages. The empirical calculation resultsshow that the rural sewage treatment facilities have a comprehensive score of more than 80 points in 7, 60-80 points in 8, with an average score of 79.05 points, and the overall performance of the score in the operation stage is better than the planning stage, and the overall operation effect was good. The calculation results were consistent with the actual operation, verifying the scientific nature and availability of the selected indices, the evaluation method constructed and the evaluation benchmark determined. The research results can provide technical methods for evaluating the operational effectiveness of rural sewage treatment facilities in similar areas and provide technical support for the planning, design, optimization, upgrading and transformation of rural sewage treatment plants.